합성 플라스틱의 생분해 - 송윤석; 이희욱; 이자현; 최한석; 최웅수; 김승욱 (한국생물공학회, 2012)
Synthetic plastics are important in many branches of industry. Although synthetic plastics provide numerous benefits, they also cause a significant environmental pollution problem because of their non-readily-biodegradability. Biodegradation may provide solution to the problem, but not enough is known about the biodegradation mechanisms of synthetic plastics. This review has been written to provide an overview of the current state of synthetic plastics (polyethylene,polyurethane, nylon, polyvinyl alcohol) biodegradation. Several biodegradation mechanisms of a few selected synthetic plastics are also presented.